ANALISIS STRATEGI PENGEMBANGAN TAMAN MARGASATWA SEMARANG - Saputra, Bagas Pramana; Yuwanto, Yuwanto; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2015)
ABSTRACTThe development of Taman Margasatwa Semarang cannot be separated from the role of various parties stakeholders (community , private , and the government) in managing to become sights of interest and comfortable and supports the conservation of nature. As the operator of Taman Margasatwa Semarang, Office of Culture and Tourism Semarang city had been trying to develop Taman Margasatwa Semarang. However, it did not have a significant result. This research used qualitative descriptive methodology and using theory of tourism development strategy to analyze development strategy of Taman Margasatwa Semarang and SWOT analysis. The main source of this research are  depth interview , photos , documents and observation.The result shows that development strategy of Taman Margasatwa Semarang based on internal factor that is either by Office of Culture and Tourism or UPTD and external factor is status changed from UPTD to Local Government Owned Company. That development strategy analyzed by the motivation factors and the inhibiting factors. Development strategy was done to restore the Taman Margasatwa Semarang as a recreation site, education, research and conservation. Hence , the suggestion after becoming Perusda is have to doing improvement and added more support infrastructure in Taman Margasatwa Semarang and do more intense cooperate with private party and animal lovers NGO to hold events regularly and promotions in order to increase attractiveness of Taman Margasatwa Semarang.Keyword : Strategy Analisys, Tourism Development